Haemonchus contortus Transthyretin-Like Protein TTR-31 Plays Roles in Post-Embryonic Larval Development and Potentially Apoptosis of Germ Cells - Shi, Hengzhi; Huang, Xiaocui; Chen, Xueqiu; Yang, Yi; Wu, Fei; Yao, Chaoqun; Ma, Guangxu; Du, Aifang (Frontiers in Cell and Developmental Biology, 2021)
Transthyretin (TTR)-like proteins play multi-function roles in nematode and are important component of excretory/secretory product in Haemonchus contortus. In this study, we functionally characterised a secretory transthyretin-like protein in the barber’s pole worm H. contortus. A full-length of transthyretin-like protein-coding gene (Hc-ttr-31) was identified in this parasitic nematode, representing a counterpart of Ce-ttr-31 in Caenorhabditis elegans. High transcriptional levels of Hc-ttr-31 were detected in the egg and early larval stages of H. contortus, with the lowest level measured in the adult stage, indicating a decreased transcriptional pattern of this gene during nematode development. Localisation analysis indicated a secretion of TTR-31 from the intestine to the gonad, suggesting additional roles of Hc-ttr-31 in nematode reproduction. Expression of Hc-ttr-31 and Ce-ttr-31 in C. elegans did not show marked influence on the nematode development and reproduction, whereas Hc-ttr-31 RNA interference-mediated gene knockdown of Ce-ttr-31 shortened the lifespan, decreased the brood size, slowed the pumping rate and inhibited the growth of treated worms. Particularly, gene knockdown of Hc-ttr-31 in C. elegans was linked to activated apoptosis signalling pathway, increased general reactive oxygen species (ROS) level, apoptotic germ cells and facultative vivipary phenotype, as well as suppressed germ cell removal signalling pathways. Taken together, Hc-ttr-31 appears to play roles in regulating post-embryonic larval development, and potentially in protecting gonad from oxidative stress and mediating engulfment of apoptotic germ cells. A better knowledge of these aspects should contribute to a better understanding of the developmental biology of H. contortus and a discovery of potential targets against this and related parasitic worms.